175k views
4 votes
(4√3 − 2√5)(3√10 + 5√6) simplify show all work

2 Answers

4 votes

Work:

Expand (4√3 − 2√5) (3√10 + 5√6) using the FOIL Method:

Apply the distributive property:

4√3 (3√10 + 5√6 ) − 2 √ 5 ( 3 √ 10 + 5 √ 6 )

4√3 (3√10) + 4√3 (5√6) − 2√5 (3√10 + 5√6)

4√3 (3√10) + 4√3 (5√6 ) − 2√5 (3√10) − 2√5 (5√6)

Simplify and combine like terms:

12√30+60√2−30√2−10√30

Subtract 10√30 from 12√30

2√30+60√2−30√2

Subtract 30√2 from 60√2

2√30+30√2

Answer:

The result can be shown in multiple forms.

Exact Form:

2√30+30√2

Decimal Form:

53.38085802

User Ralfs
by
5.8k points
5 votes

Answer:

2√30 + 30√2

Explanation:

(4√3 − 2√5)(3√10 + 5√6) simplify

=======

  • (4√3 − 2√5)(3√10 + 5√6)=
  • 12√30 + 20√18 - 6√50 - 10√30=
  • 2√30 + 20*3√2 - 6*5√2=
  • 2√30 + 30√2
User YosiFZ
by
6.6k points